The role of SGLT2i in attenuating residual cardiovascular risk through blood pressure-lowering: mechanistic insights and perspectives - Barreto, Joaquim; Campos-Staffico, Alessandra M.; Nadruz, Wilson; Quinaglia, Thiago; Sposito, Andrei C. (Frontiers in Clinical Diabetes and Healthcare, 2023)
Sodium glucose cotransporter 2 inhibitors (SGLT2) have been increasingly pursued as a promising target for addressing residual cardiovascular risk. Prior trials demonstrated that SGLT2i not only promotes glucose-lowering, but also improves endothelial dysfunction, adiposity, fluid overload, and insulin sensitivity thus contributing to hemodynamic changes implicated in its cardiorenal benefits. The mechanisms in the effect of SGLT2i on blood pressure and their potential role in preventing cardiovascular events are hereby revised.